Zeaxanthin improves diabetes-induced cognitive deficit in rats through activiting PI3K/AKT signaling pathway - Zhou, Xiaoyan; Wang, Shanshan; Ding, Xin; Qin, Li; Mao, Yizhen; Chen, Lei; Li, Wei; Ying, Changjiang (Brain research bulletin, 2017)
•Diabetes- induced cognitive deficit could be ameliorated by zeaxanthin.•Zeaxanthin could protect hippocampal neurons against hyperglycemia.•Zeaxanthin improved cognitive deficit through activating PI3K/AKT signaling pathway. Published studies have shown that cognitive deficit is a characteristic manifestation of neurodegenerative disease in diabetes. However, there is no effective prevention and treatment for this diabetes-associated behavior disorder. In the present study, we attempted to elucidate the effect of zeaxanthin on cognitive deficit and the change in the hippocampus correlated with cognitive decline in diabetic rats. Diabetic rats in this study were induced by high-fat diet and low-dose streptozocin (STZ), cognitive ability of rats were evaluated use morris water maze (MWM) and morphology change in hippocampus was assessed by cresyl violet stain. Moreover, we detected the expression of phosphorylated serine/threonine kinase (p-AKT) and Cleaved caspase-3, and the activity of nuclear factor-κB (NF-κB) use western-blot (WB). Results displayed that supplementation with zeaxanthin reduce blood glucose, improve cognitive deficit, survive neural cell, increase p-AKT level, inhibit Cleaved caspase-3 level and NF-κB nuclear transcription in hippocampus. This study demonstrated that zeaxanthin ameliorate diabetes-related cognitive deficit may by means of protecting neural cell from hyperglycemia involved in AKT/NF-κB signaling pathway. This study may provide a potential therapeutic approach for the prevention of diabetes- associated cognitive deficit.